Investigation on Premixed Hydrogen/air Explosion in Closed Pipeline - Siti Zubaidah, Sulaiman; R. M., Kasmani; A., Mustafa (2014)
The acceleration of flame inside a pipe is a complex phenomenon involving several variables spanning from fuel nature, mixture composition and geometrical characteristics of the pipe itself such as length, wall roughness or presence of obstacles. One of the key parameters governing the process of flame acceleration is the presence of obstacles in pipe. Extensive studies have been carried out to investigate the profiles of flame propagation and maximum pressure performed in pipe with of 90 degree bend. This work seeks to evaluate the magnitude of the hydrogen-air mixture explosion using 90 degree pipe configuration as a full bore obstacle condition. The data covers a wide range of hydrogen concentration between 13 to 54 % v/v (equivalence ratio, = 0.6-1.4). The experimental work was performed in a closed pipe of length to diameter ratio (L/D) of 51 with a volume of 0.42 m3, operating at ambient conditions. From the result, it was observed that the highest explosion severity occurred at slightly rich concentration (=1.2) or 36% v/v. It is worth to note that the pressure downstream of bend gave about 2 times higher compared to the pressure observed at the bend. This is due to the retonation effect, causing the flame intensification and intense turbulent towards the end wall and this phenomenon is highlighted.